PENGARUH CURRENT RASIO, RETURN ON EQUITY, RETURN ON ASSETS, EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Tukirah, 10.05.52.0139; Maryono, Maryono (Students Journal of Accounting and Banking, 2014)
The research aims to identify and analyze the effect of Current Ratio, Return on Equity, Return on Assets, Earning Per Share on Stock Prices of manufacturing industrythat listed on Indonesian Stock Exchange. The population in this research are all manufacturing companies whose shares are listed on the Indonesia Stock Exchange during the period 2010-2012. Sampling technique used was purposive sampling. There is 74 companies that can be analysed. This study is analyzed by using multiple regression. The multiple regression shows that Current Ratio significant positive effect on stock price, Return on Equity, significant positive effect on stock price, Return on Assets, havenât significant positive effect on stock price, and Earning Per Share, significant positive effect on stock price.Keywords: Current Ratio, Return on Equity, Return on Assets, Earning Per Share and Stock Price